Fabrication of Polyvinylsilazane and SiC/Si3N4 Ceramic Microspheres - Liu, Hongli; Kang, Wei; Li, Jing; Zhou, Cailou (Asian Journal of Chemistry, 2014)
The polyvinylsilazane microspheres were synthesized using polyvinylsilazane as precursor by emulsification technology. The effect of operating conditions on the morphology and size of the polyvinylsilazane microspheres were investigated by SEM. The polyvinylsilazane microspheres were then converted to SiC/Si3N4 ceramic microspheres through pyrolysis at 800-1400 °C under nitrogen atmosphere. The resultant ceramic microspheres kept their dense spherical shape with about 14 % linear shrinkage. The morphology and pyrolysis process were characterized by FTIR, TGA, SEM, TEM and XRD. This technique can be further extended to other preceramic polymers and can be used to prepare single/multi-material ceramic microspheres.